2000
DOI: 10.1002/1097-4652(200011)185:2<253::aid-jcp10>3.3.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of lung epithelial cells in response to TNF‐α requires angiotensin II generation de novo

Abstract: Recent work from this laboratory demonstrated that apoptosis of pulmonary alveolar epithelial cells (AEC) in response to Fas requires angiotensin II (ANGII) generation de novo and binding to its receptor (Wang et al., 1999b, Am J Physiol Lung Cell Mol Physiol 277:L1245-L1250). These findings led us to hypothesize that a similar mechanism might be involved in the induction of AEC apoptosis by TNF-alpha. Apoptosis was detected by assessment of nuclear and chromatin morphology, increased activity of caspase 3, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Very recent data from our laboratories using a rabbit model of MAS indeed indicate that captopril and inhibition of AT receptor action may in fact diminish pulmonary epithelial apoptosis in meconium lungs (31, 40). Additional data from our laboratory show that cytokine‐treated rabbit lung and human lung airway epithelial cell line A549 demonstrate a similar rate of lung apoptosis, compared to meconium‐instilled lungs (37, 41).…”
Section: Meconium‐induced Apoptosismentioning
confidence: 86%
“…Very recent data from our laboratories using a rabbit model of MAS indeed indicate that captopril and inhibition of AT receptor action may in fact diminish pulmonary epithelial apoptosis in meconium lungs (31, 40). Additional data from our laboratory show that cytokine‐treated rabbit lung and human lung airway epithelial cell line A549 demonstrate a similar rate of lung apoptosis, compared to meconium‐instilled lungs (37, 41).…”
Section: Meconium‐induced Apoptosismentioning
confidence: 86%
“…These peptides then act via ACE and AT1 to promote proliferation of FB PA. This mechanism has also been observed in lung fibrosis, in which interstitial fibroblasts can produce Ang II precursors (angiotensinogen, angiotensin I) for paracrine signaling (49)(50)(51)(52)(53). This up-regulation of the Ang-ACE system also plays a central role in development of pulmonary hypertension (17,20,27,54).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Konigshoff et al [43] have identified the localization of both AT 1 and AT 2 receptors to interstitial fibroblasts in fibrotic human lung samples. Wang et al [45][46][47] have demonstrated that activation of apoptosis, thought to be a critical event in developing fibrosis, via Fas [45,46] and TNF-α [47] is AngII-dependent. Wang et al [45][46][47] have demonstrated that activation of apoptosis, thought to be a critical event in developing fibrosis, via Fas [45,46] and TNF-α [47] is AngII-dependent.…”
Section: Ras and Fibrosismentioning
confidence: 99%